Peran Artificial Intelligence sebagai Strategi Inovatif dalam Penguatan Talent Management dan Peningkatan Kompetensi SDM di Era Pendidikan 5.0 - Sutrisno, Sutrisno; Permana, Riko Mersandro (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to examine the role of AI as an innovative strategy in strengthening talent management and enhancing human resource (HR) competence in the era of Education 5.0. This research employs a literature review method using a qualitative approach and descriptive analysis, where data were collected from scientific articles obtained through Google Scholar and other credible websites during the period 1964–2025. From a total of 50 articles identified, a rigorous selection process based on relevance and validity was conducted, resulting in 23 articles used as the main sources of analysis. The findings reveal that AI plays a significant role in optimizing the processes of talent identification, development, and retention through data-driven analytics systems, adaptive learning, and AI-powered human resource analytics. This study also emphasizes the importance of integrating Human Capital Theory, the Talent Management Framework, and Social Cognitive Theory in explaining the interrelationship between technology and human competence development. AI functions as a strategic partner in creating an innovation-oriented, sustainable, and human-centered ecosystem for education and human resource management in the era of Education 5.0.